2014
DOI: 10.1016/j.jdeveco.2013.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Automatic grade promotion and student performance: Evidence from Brazil

Abstract: This paper examines the effect of automatic grade promotion on academic achievement in 1,993 public primary schools in Brazil. A difference-in-differences approach that exploits variation over time and across schools in the grade promotion regime allows the identification of the treatment effect of automatic promotion. I find a negative and significant effect of about 7% of a standard deviation on math test scores. I provide evidence in support of the interpretation of the estimates as disincentive effect of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 22 publications
0
18
1
6
Order By: Relevance
“…These findings are consistent with Ndaruhutse (2008) who found that countries implementing automatic promotion (including Sub-Saharan Africa countries) produced higher learning results compared with those that practice repetition. However, the results are contrary to Koppensteiner (2014) who found a negative and significant effect on 4 th grade learning achievements of about 6% of a standard deviation attributed to automatic grade promotion in Brazil. One of the possible reasons for the difference in the effect at P3 and P6 is the difference in students' school/ classroom attendance patterns.…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…These findings are consistent with Ndaruhutse (2008) who found that countries implementing automatic promotion (including Sub-Saharan Africa countries) produced higher learning results compared with those that practice repetition. However, the results are contrary to Koppensteiner (2014) who found a negative and significant effect on 4 th grade learning achievements of about 6% of a standard deviation attributed to automatic grade promotion in Brazil. One of the possible reasons for the difference in the effect at P3 and P6 is the difference in students' school/ classroom attendance patterns.…”
Section: Resultscontrasting
confidence: 99%
“…Contrary to the above scholars, Koppensteiner (2014) in his study on the relationship between automatic promotion and learning achievements in Brazil found a negative and significant effect of about 6% of a standard deviation. Findings by Taye (2003) on the impact of automatic promotion on learning outcomes in Ethiopia showed that 90.4% of the teachers interviewed said grade retention is better than automatic promotion to help underachieving students perform better in latter grades.…”
Section: Review Of Previous Studiesmentioning
confidence: 65%
See 2 more Smart Citations
“…Fundamental e da Valorização do Magistério (Fundef), a federal fund which had as its aim the redistribution of state and municipal resources back to municipalities according to student enrolment (Koppensteiner, 2014). Our hypothesis is that municipalities that received higher government spending on primary education had higher Prova Brasil scores.…”
Section: Independent Variable Of Interest Is the Fundo De Desenvolvimmentioning
confidence: 90%